Research Trend On Healthcare (Hospital Financial) Failure And Activity-Based Costing Methods: A Bibliometric Analysis - Dany, Yurisal Akhmad; Pribadi, Firman (Jurnal Riset Kesehatan, 2024)
Hospital financial failure means bankrupt in economic point-of-view. While from the patient care perspective, it can compromise healthcare delivery and deliver possible harm due to substandard services. Leveraging digitalization and information technology can significantly enhance financial management, improve efficiency, and ultimately support sustainable healthcare services. This bibliometric analysis through Scopus database. Retrieved articles were examined based on annual publication numbers, contributing countries, subject areas, authors, and cited documents. Visual analysis was done using VOSviewer to provided insights into word co-occurrence in clusters and R Studio's Bibliometrix package was employed to identify the most contributing countries and the most cited publications. The analysis on total 429 articles revealed that healthcare and activity-based costing is an emerging trend, with a growing number of publications each year. The United States emerged as the leading country in this research area, though other nations also contributed significantly. Medicine was identified as the most common subject area. VOSviewer analysis identified seven clusters related to the topic. Activity-based costing has evolved to accurately assess product costs in changing business landscapes, particularly in healthcare, where it helps optimize profits. The findings indicate a growing awareness of the importance of financial management in sustaining healthcare services globally. However, the study's reliance on a single database and lack of a comprehensive systematic review limit its scope, potentially excluding relevant research from other sources.